Learning Losses in Pakistan Due to COVID-19 School Closures : A Technical Note on Simulation Results - Geven, Koen (World Bank, Washington, DC, 2020)
Pakistan was among the first countries in the world to institute widespread school closures as a result of Coronavirus 2019 (COVID-19). What are the expected levels of learning that teachers will have to deal with in the class? Will children have lost learning while schools were closed? What should teachers, parents, and children expect from the first few weeks of schooling? How can parents, teachers, and the school system as a whole help children catch up? While school closures have been effective in supporting efforts at social distancing, they may well have serious consequences for schooling and learning. This note presents results from a series of simulations that aim to capture the impacts that school closures in Pakistan may have on the learning levels, enrollment, and future earnings of children and students. In this note, the authors present an overview of how these numbers are calculated and how to interpret them. This note draws on a simulation exercise for all countries on which data is available, including Pakistan, conducted by researchers at the World Bank.